Intra-arrest cooling with delayed reperfusion yields higher survival than earlier normothermic resuscitation in a mouse model of cardiac arrest - Zhao, Danhong (2007)
BACKGROUND: Therapeutic hypothermia (TH) represents an important method to attenuate post-resuscitation injury after cardiac arrest. Laboratory investigations have suggested that induction of hypothermia before return of spontaneous circulation (ROSC) may confer the greatest benefit. We hypothesized that a short delay in resuscitation to induce hypothermia before ROSC, even at the expense of more prolonged ischemia, may yield both physiological and survival advantages. METHODS: Cardiac arrest was induced in C57BL/6 mice using intravenous potassium chloride; resuscitation was attempted with CPR and fluid administration. Animals were randomized into three groups (n=15 each): a normothermic control group, in which 8 min of arrest at 37°C was followed by resuscitation; an early intra-arrest hypothermia group, in which 6.5 min of 37°C arrest were followed by 90 sec of cooling, with resuscitation attempted at 30°C (8 min total ischemia); and a delayed intra-arrest hypothermia group, with 90 sec cooling begun after 8 min of 37°C ischemia, so that animals underwent resuscitation at 9.5 min. RESULTS: Animals treated with TH demonstrated improved hemodynamic variables and survival compared to normothermic controls. This was the case even when comparing the delayed intra-arrest hypothermia group with prolonged ischemia time against normothermic controls with shorter ischemia time (7 day survival, 4/15 vs 0/15, p<0.001). CONCLUSIONS: Short resuscitation delays to allow establishment of hypothermia before ROSC appear beneficial to both cardiac function and survival. This finding supports work suggesting that post-resuscitation injury processes begin immediately after ROSC, and that intra-arrest cooling may serve as a useful therapeutic approach to improve survival.